2022
DOI: 10.1097/rlu.0000000000004032
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immune Response Syndrome After COVID-19 Immunization—Initial and Follow-up 18F-FDG PET/CT Imaging Appearances

Abstract: A 46-year-old woman with previous history of breast cancer had follow-up 18 F-FDG PET/CT 5 days after COVID-19 vaccination. In addition to avid axillary nodes, a well-documented feature, the scan demonstrated diffuse splenic and marrow uptake. Clinical history, laboratory, and scan findings were in keeping with SIRS (systemic inflammatory response). The patient recovered with supportive management. On follow-up, 18 F-FDG PET/CT imaging 3 months later features had r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
(22 reference statements)
1
11
0
Order By: Relevance
“…Although exceptional cases of diseases occurred or worsened apparently after COVID-19 vaccination have been described in PET/ CT literature [19][20][21][22][23][24][25][26][27][28][29][30][31][32], none of the included studies reported findings suggestive for systemic reaction. The only exception was the study of Siripongsatian et al [18] who specifically evaluated a small series of patients who experienced neurological symptoms after COVID-19 vaccination. All types of COVID-19 vaccine, boosting a protective immune response through the production of neutralizing antibodies targeting SARS-CoV-2 spike S membrane glycoprotein [33], safely and positively impact on individual and global health, reducing the risk of severe infections.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although exceptional cases of diseases occurred or worsened apparently after COVID-19 vaccination have been described in PET/ CT literature [19][20][21][22][23][24][25][26][27][28][29][30][31][32], none of the included studies reported findings suggestive for systemic reaction. The only exception was the study of Siripongsatian et al [18] who specifically evaluated a small series of patients who experienced neurological symptoms after COVID-19 vaccination. All types of COVID-19 vaccine, boosting a protective immune response through the production of neutralizing antibodies targeting SARS-CoV-2 spike S membrane glycoprotein [33], safely and positively impact on individual and global health, reducing the risk of severe infections.…”
Section: Discussionmentioning
confidence: 99%
“…Positive lymph nodes were observed less frequently in elderly (≥ 64 years) patients, and although after the second injection a second peak of incidence was observed in great elders (≥ 85 years), this datum should be carefully interpreted due to the small sample size. After the second injection, [ 18 and larger than after the first administration with a higher percentage of grades 3 (14 and 8%, respectively) and 4 (13 and 4%, respectively). Skawran et al [9] compared the inflammatory reaction observed after Pfizer-BioNTech and Moderna vaccinations in patients examined with [ 18 F]FDG PET/CT.…”
Section: Local Signs Of Inflammationmentioning
confidence: 97%
See 3 more Smart Citations